Pengembangan Keterampilan Berwirausaha Melalui Diversifikasi Produk Olahan Daun Kelor Sebagai Inovasi Makanan Sehat Untuk Pencegahan Stunting Di SMK Muhammadiyah 5 Kisaran - Sahla, Hilmiatus; Andriani, Dian Ayu; Siregar, Aris; Lubis, Alweni Khoiriyah; Wahyuni, Sri; Khulsum, Umi (Yayasan Rahmat Islamiyah, 2024)
In the curriculum at SMK Muhammadiyah 5 Kisaran, entrepreneurship lessons are a subject that should be followed by every student, Himbauan from the district government of Asahan on early stunting prevention by doing Development of entrepreneurial skills through diversification of leaf processing products as a healthy food innovation for stopping prevention. The problems faced by the students already have a conceptual understanding of entrepreneurship but not the maximum in entrepreneurial practice, so it is necessary to develop entrepreneur skills through diversification of leaf processing products as a healthy food innovation for the prevention of early stunting. The solution offered by the Community Partnership Program (CMP) Scheme is to provide some training to partners in developing the skills of entrepreneurial partners through the diversification of processed products by making stick leaves.